Need for Newer Perspectives on Violence: A Subaltern View - Chakravartty, Avaniendra (Social Inquiry: Journal of Social Science Research, 2023)
This article explains the intricate relationship between violence and health, aiming to transcend the conventional and restricted perspectives through which violence is typically perceived and conceptualized. The limitation regarding the conceptualisation of violence, by researchers, when the Sapir-Whorf hypothesis is taken into consideration, leads us to think that those researching violence and health are limited to the WHO definition and conceptualisation of violence due to various historical processes of knowledge production and flows, which leads to a ‘violence of closure’. I follow a reflexive approach and identify several types of violence from which I focus on cognitive violence, epistemic violence, ontological violence, and neoliberal violence. Understanding of violence needs to acknowledge that multiple forms of violence overlap entangle and intersect in a rhizomatic manner. Only sticking to the WHO definition of violence leads to a condition that creates a condition of ‘violence of closure’ that neglects various systemic and structural processes through which violence is experienced at the individual micro-level.